2006
DOI: 10.1590/s1516-44462006005000018
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and fecundity of an outpatient sample with schizophrenia

Abstract: Patients with schizophrenia showed lower rates for marital status, fertility and fecundity when compared to standard population rates. However, many patients will become parents during their life time. Therefore, it is imperative to develop services that fulfill their needs, mainly in Brazil, a middle-income country, where resources are scarce and there is no policy for dealing with this reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…Essa divergên-cia pode ser explicada devido à diferença dos diagnósticos dos pacientes estudados, uma vez que nos outros estudos os pacientes eram em sua totalidade ou majoritariamente da categoria diagnóstica de esquizofrenia, transtornos esquizotípicos e transtornos delirantes, enquanto neste estudo a maioria dos pacientes possuía diagnóstico na categoria de transtornos do humor e afetivos. Segundo Terzian et al 23 , pacientes com esquizofrenia mostraram menores taxas de casamento quando comparados com taxas populacionais. Dessa forma, esses pacientes ficam comumente sob os cuidados de seus pais, uma vez que as características da doença implicam consequências que se refletem em diversos aspectos da vida do paciente, inclusive na vida afetiva e social 24 .…”
Section: Resultsunclassified
“…Essa divergên-cia pode ser explicada devido à diferença dos diagnósticos dos pacientes estudados, uma vez que nos outros estudos os pacientes eram em sua totalidade ou majoritariamente da categoria diagnóstica de esquizofrenia, transtornos esquizotípicos e transtornos delirantes, enquanto neste estudo a maioria dos pacientes possuía diagnóstico na categoria de transtornos do humor e afetivos. Segundo Terzian et al 23 , pacientes com esquizofrenia mostraram menores taxas de casamento quando comparados com taxas populacionais. Dessa forma, esses pacientes ficam comumente sob os cuidados de seus pais, uma vez que as características da doença implicam consequências que se refletem em diversos aspectos da vida do paciente, inclusive na vida afetiva e social 24 .…”
Section: Resultsunclassified
“…This finding was not expected in the current study as schizophrenic and patients with chronic pain are generally not married. [33][34][35][36] With regard to the environmental domain, patients in this study had lower scores for both groups when compared to other studies, and these scores were lower than those found in China (score = 15.0) and Malaysia (score = 14.0). 28,29 A study conducted across 15 regions in Italy also found results that were far superior in all domains, in particular the social and environmental domains, to the current study's results.…”
Section: 10mentioning
confidence: 56%
“…Таким образом, дли-тельный (в течение 78 поколений) отбор крыс на проявле-ние кататонической реакции привел к координированному снижению целого комплекса репродуктивных параметров у взрослых самцов и уменьшению фертильности крыс. В некоторых работах отмечается, что у людей, страдаю-щих психическими отклонениями, в частности шизофре-нией и депрессией, ослаблены сперматогенная (Worly, Gur, 2015) и гормональная (Markham, 2012) функции семен-ников, а также снижена демографическая фертильность (Terzian et al, 2006). Эти эффекты авторы связывают с не-гативным влиянием социальной среды или воздействием препаратов, используемых для коррекции поведения.…”
Section: Discussionunclassified